(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Alexandra Yu. Chernysheva (Rostov-on-Don, Russian Federation) In this article we analyze the military event interpretation in the reportage on war. It is first of all the ideologically colored process aimed at the formation of mass consciousness and public opinion. The reportage on war reflects consistently the journalism informational and communicative characteristics which are covered into the ideological language forms. We interpret these forms as the specific social practice based on the target auditorium persuading, organizing the interactive dialogue between the journalist and the reportage consumer. All this makes the «new» discursive parameters of the contemporary reportage on war. The Media turns out to be «sandwiched» between the promotional activities of the political actors involved in the military conflict that appears to be a direct consequence of changes in the current understanding of such concept as «the peace in contemporary wars». The military conflict participants and the political actors behind them are making strong attempts to influence the media and to determine the nature of their news reports. Key words: reportage on war, propaganda, war framing, enemy image, fictionalization, manipulative language.